The relationship between national identity and European Union evaluations, 1993–2017. (September 2019) - Clark, Nicholas J; Rohrschneider, Robert
We examine two aspects of the connection between individuals' national identities and their European Union evaluations. First, we examine the changing relationship from 1993–2017, thus paying attention to not only recent crises years but also the time when political integration accelerated after the Maastricht treaty came into effect. Second, we draw on group-identity theory to explain the changing relationship for individuals with extreme as well as moderate ideological attitudes. We use a new cumulative Eurobarometer Representation dataset (1993–2017) to test three hypotheses. Our most important finding is that by 2017 the relationship between national identity and European Union evaluations among ideologically moderate citizens is stronger than it was in 1993 among individuals with right-extreme ideological views. While the economic crisis since 2007 reinforced this development, it was not responsible for its onset.